Attenuation of pressure dips underneath piles of spherocylinders. Issue 21 (21st May 2018) - Zhao, Haiyang; An, Xizhong; Gou, Dazhao; Zhao, Bo; Yang, Runyu
Abstract : The discrete element method (DEM) was used to simulate the piling of rod-like (elongated sphero-cylindrical) particles, mainly focusing on the effect of particle shape on the structural and force properties of the piles. Abstract : The discrete element method (DEM) was used to simulate the piling of rod-like (elongated sphero-cylindrical) particles, mainly focusing on the effect of particle shape on the structural and force properties of the piles. In this work, rod-like particles of different aspect ratios were discharged on a flat surface to form wedge-shaped piles. The surface properties of the piles were characterized in terms of angle of repose and stress at the bottom of the piles. The results showed that the rise of the angle of repose became slower with the increase of particle aspect ratio. The pressure dip underneath the piles reached the maximum when the particle aspect ratio was around 1.6, beyond which the pressure dip phenomenon became attenuated. Both the pressure dip and the shear stress dip were quantitatively examined. The structure and forces inside the piles were further analyzed to understand the change in pressure dip, indicating that "bridging" or "arching" structures within the piles were the cause of the pressure dip.